Citizen Role Representation in Digital Government Maturity Models: A Systematic Review - Qurrota Ayun Majid; Dana Indra Sensuse (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
This study investigates how citizen roles are represented and structurally positioned within Digital Government Maturity Models (DGMMs). Using a Systematic Literature Review guided by Kitchenham’s protocol, the review analyzed studies published between 2020 and 2025 across seven major academic databases. From 900 initial records, 14 studies met the inclusion and quality criteria. Through backward tracing, policy reference analysis, and cross-model extraction, these studies produced 77 DGMMs as the final units of analysis. The models were examined using a role-based analytical lens that classifies citizen representation into five levels: None, Limited, Implicit, Explicit, and Strong. The findings show that the Limited category remains dominant, indicating that most DGMMs still position citizens mainly as end-users or service recipients rather than active participants in digital governance processes. However, the increasing presence of Explicit and Strong models reflects a gradual shift toward participatory, collaborative, and citizen-centric digital governance. This study contributes by proposing a typology of citizen role representation that extends prior descriptive mappings into a deeper structural evaluation of how citizen participation, engagement, and co-creation are embedded within digital maturity